2014
DOI: 10.1016/j.ijid.2013.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent dengue and malaria infection in Lahore, Pakistan during the 2012 dengue outbreak

Abstract: The rate of isolated malaria and dengue-malaria co-infection was high in probable cases of dengue fever in our study. Except for jaundice, we could not find any significant between-group differences in the severity of the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
48
6

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(68 citation statements)
references
References 7 publications
9
48
6
Order By: Relevance
“…Present study also reports only 2 cases of concurrent dengue and malaria infections. In contrast to our findings a study from Lahore, Pakistan reported high proportion of denguemalaria co-infections (17/52) during 2012 outbreaks of Dengue infection (12). Both RDTs were found to be negative in isolated malaria infections in present study.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…Present study also reports only 2 cases of concurrent dengue and malaria infections. In contrast to our findings a study from Lahore, Pakistan reported high proportion of denguemalaria co-infections (17/52) during 2012 outbreaks of Dengue infection (12). Both RDTs were found to be negative in isolated malaria infections in present study.…”
Section: Resultscontrasting
confidence: 99%
“…Dengue NS1 antigen and Dengue specific IgA antibody based assays have been shown to be useful during early febrile days. [5][6][7][8][9][10][11][12][13][14][15][16][17] ELISA and ICT based NS1 assay have been used as a diagnostic tool during febrile phase till defervescence (1 -9 days of fever onset) however, due to presence of virus -IgG immunocomplexs this assay has shown to be less sensitive in secondary infection as compared to primary infections 18,19 and may give false negative results in dengue endemic and hyperendemic areas. Studies comparing sensitives and specificities of IgA and NS1 reported dengue IgA to be more sensitive during early febrile phase of both primary and secondary dengue infection.…”
Section: -416mentioning
confidence: 99%
“…There were isolated case reports in India [7, 20–24], East Timor [12], Japan [17], Bangladesh [13], Indonesia [14], Malaysia [16], and Cambodia [15]. Following that, a series of cases were reported in French Guiana [25, 26], Brazil [11, 27], India [2830], Bangladesh [31], Pakistan [10], Peru [32], and Kenya [33]. …”
Section: Discussionmentioning
confidence: 99%
“…Studies were conducted regionally and it was noticed that the incidence of dual malaria-dengue co-infection among patients presented with acute febrile illness was actually higher than expected, ranging from 1 to 33% of the acute febrile illness state in different countries [810, 26, 33]. This increase may be explained by the overlap of vectors in endemic areas and increased prevalence of dengue fever [9, 26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation